Laying Foundation to Advertisement Genre: An Analysis of Job Advertisement Discourse Made by the Royal Civil Service Commission of Bhutan - Dendup, Pema (Universitas Lancang Kuning, 2021)
To lay foundation in the literature related to the genre of advertisements, this paper is a synchronic approach to study the job advertisements made by the Royal Civil Service Commission (RCSC) of Bhutan. RCSC is the major recruiting agency of civil servants into a government job. As mandated, RCSC recruits thousands of fresh employees annually. RCSC features its job-related announcements in the media, mainly the Bhutan Broadcasting Service, the mainstream media and also in its official website. The data of this study was the ‘Vacancy Announcement’ dated January 8, 2020, featured in RCSC website and the analysis of the data was based on Swale’s (1990) Six Defining Characteristics of Discourse Community. The results showcased Bhutan as a bilingual society for informing the citizens as the job advertisements were delivered in both Dzongkha and English. RCSC’s format of job advertisement employed the common format used by most of the organisations. This study points that there is a need to look into some elements used by other organisations. Therefore, this study recommends RCSC, as the major recruiting agency in Bhutan, to incorporate other missing elements of job advertisement.